Extending the remit of evidence-based policing - Brown, Jennifer (International journal of police science & management, 2018)
Evidence-based policing (EBP) is an important strand of the UK’s College of Policing’s Police Education Qualifications Framework (PEQF), itself a component of a professionalisation agenda. This article argues that the two dominant approaches to EBP, experimental criminology and crime science, offer limited scope for the development of a comprehensive knowledge base for policing. Although both approaches share a common commitment to the values of science, each recognizes their limited coverage of policing topics. The fundamental difference between them is what each considers ‘best’ evidence. This article critically examines the generation of evidence by these two approaches and proposes an extension to the range of issues EBP should cover by utilizing a greater plurality of methods to exploit relevant research. Widening the scope of EBP would provide a broader foundational framework for inclusion in the PEQF and offers the potential for identifying gaps in the research, constructing blocks for knowledge building, and syllabus development in higher level police education.